Gestão de global sourcing em empresas multinacionais com unidades produtivas em mercados emergentes: caso das subsidiárias brasileiras - Ricardo, Alexandre (Universidade do Vale do Rio dos Sinos, 2012)
The growing competition for consumer markets, driven by globalization, has required organizations to put in practice strategies to support new business conditions in order to keep its market share and provide continuous growing. In this context, we highlight the needs to implement strategies and processes to have efficient management between headquarters and subsidiaries, highlighted the management of supply. This paper is focused on the management of global sourcing. The aim of the research was to perform analysis of how the production subsidiaries of foreign multinationals, operating in Brazil, are embedded and attend to organizations global sourcing strategies. Initially, an extensive literature research on the global sourcing strategy was made, which identified a gap related to the interaction of the subsidiary in the overall supply. Previous studies have been focused on the organization world headquarters, strategies to implement and manage global sourcing. The field research was adopted as a research method, using visits, and semi-structured interview in-depth with local supply managers, and documentary research. Sample was composed of eight foreign multinational companies with production facilities in Brazil. Different stages of the purchasing function have been identified, according to stage model proposed by Monczka e Trent (2003a). Most of them were characterized by organizational arrangements, management and control forms classified in global sourcing strategy, and significantly less, companies operating at the level of international purchases. Noteworthy, it was identified in most of companies visited, that production subsidiary participation is partially aligned with the strategy of global sourcing, reactive to the demands from world headquarters. The study suggests that local production subsidiaries should review its approach related to the global sourcing management, becoming more proactive, aligned with the organization global sourcing strategy, as well as serving in their level of expertise, best practices referenced in the literature.
Keywords: Subsidiárias de produção; Estratégias de fornecimento; Global sourcing; Empresas multinacionais; Production subsidiaries; Supply strategies; Multinational companies; ACCNPQ::Ciências Sociais Aplicadas::Administração